Regulations on combating epidemic threats in Poland and COVID-19 pandemic - review and assessment of implemented solutions - Klaudia Aneta Alcer; Anita Błachut; Piotr Romaniuk (Śląski Uniwersytet Medyczny w Katowicach, 2023)
The COVID-19 pandemic had a major impact on the functioning of the entire world, and the consequences of this event are still visible in various aspects of the functioning of countries. As a countermeasure against such a crisis, Poland implemented regulations to help combat the negative effects or minimize them. The aim of the study is to evaluate the anti-epidemic regulations and their changes during the pandemic. The acts were reviewed by means of the Internet System of Legal Acts (Internetowy System Aktów Prawnych - ISAP) and the Public Information Bulletin (Biuletyn Informacji Publicznej - BIP) database. The anti-epidemic regulations in Poland propose solutions that may help in counteracting a pandemic both in the sphere directly related to medical aspects, as well as social and entrepreneurial or economic aspects. However, the analysis of relevant regulations and literature revealed a large mismatch between the existing regulations and the actual needs related to real epidemiological phenomena. The first weeks of the pandemic, especially in the area of applying these standards, revealed a great deal of chaos. The standards introduced during the pandemic were also characterised by a number of inaccuracies and ambiguities. An attempt should be made to create a more coordinated plan for an eventual subsequent pandemic and an evaluation of the rules for other emergencies should be undertaken to avoid the mistakes and chaos witnessed in the COVID-19 pandemic.